Effects of aromatase inhibition vs. testosterone in older men with low testosterone: randomized‐controlled trial. (20th November 2015) - Dias, J. P.; Melvin, D.; Simonsick, E.M.; Carlson, O.; Shardell, M.D.; Ferrucci, L.; Chia, C. W.; Basaria, S.; Egan, J. M.
Summary: Aging in men is associated with loss of bone mass, impaired physical function and altered body composition. The objective of this proof‐of‐concept randomized, double‐blind, placebo‐controlled, parallel‐group, single‐center trial was to determine the relative effects of testosterone (T) and estradiol (E2 ) on bone mineral density, body composition, and physical performance in older men. The primary outcome was lumbar spine bone mineral density (BMD), and secondary outcomes were body composition, muscle strength, gait speed, and sex hormone concentrations. Forty three men (age range, 65–82 years; mean age 71 years) with low total T levels <350 ng/dL were randomized to one of three groups: 5 g transdermal testosterone gel (TT) ( N  = 16), anastrozole (AI) 1 mg ( N  = 14) or placebo daily ( N  = 13) for 12 months. Outcomes were assessed at baseline, 3, 6, and 12 months. Both TT and AI increased serum TT levels (>500 ng/dL, p  < 0.05) compared to baseline; T values remained stable throughout the duration of the trial. At 12 months, TT improved the primary outcome of lumbar spine BMD ( p  < 0.01).Both interventions improved knee strength at 12 months compared to baseline ( p  < 0.05) while lean body mass significantly increased only in the AI group at 6 and 12 months (1.49 ± 0.38 kg, p  < 0.01; 1.24 ± 0.39 kg, p  < 0.05, respectively) compared to baseline. Interestingly, TT improved fast gait speed at 3 and 12 months ( p  < 0.01, p  < 0.05, respectively). In summary, this proof‐of‐concept study confirms that aromatization of T is required for maintaining BMD in older men with low‐T levels. The trial also uncovered the novel finding that aromatization of T is required for improvement in fast gait speed, an observation that needs to be verified in future studies.